Performances sonoras: uma escuta do cotidiano goianiense - Oliveira, Thais Rodrigues (2019)
The research here systematized circumscribes the problem: do the sounds of daily life in the the city represent us culturally? There is a sound cultural performance of Goiânia? Therefore, our objective was to identify, collect and record sounds in four significant places of the city and, subsequently, edit them in order to make a sound installation called Windows Sounds. This installation, beyond the end in itself, also served as a mecanism to confirm or not whether there is a cultural sound performance in Goiânia, with the reception of the selected sounds. The research data were obtained through observation, listening, interview and questionnaires of the four most expressive sound territories of Goiânia, selected and considered that way by me. Data analisys was developed qualitatively, etnographic (with contributions of urban antropology) and based on theoretical discussions of these authors: Erving Goffman (1986, 2001, 2011, 2012); Richard Schechner (1985, 2002, 2003, 2006); Raymond Murray Schafer (1977, 2011); Victor Turner (1974, 1982), Sainy Veloso (2013, 2014); Roland Barthes (1990); Michael Certeau, Luce Giard and Pierre Mayol (1996); Clifford Geertz (1989); Carlos Fortuna (1998, 1999); José Guilherme Cantor Magnani (1998, 2007, 2013, 2016); Maurice Halbwachs (1980); Pierre Schaeffer (1950, 1966); Bernd Schulz (1999); Gilles Deleuze and Felix Guattari (1992), among others. We hope that this sensitive sound experience, conducted in the investigation, will contribute to the discussion of sounds as cultural sound performance and allow understanding the local culture in its diversity.